Profitabilitas sebagai Mediator Pengaruh Good Corporate Governance dan Corporate Social Responsibility terhadap Nilai Perusahaan : (Studi pada Sektor Barang Konsumsi di BEI Periode 2020-2024) - Irma Fernanda Devi; Ahmad Idris (Owner : Riset dan Jurnal Akuntansi, 2025)
This study  empirically analyze the mediating role of profitability on the relationship between Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on Firm Value. Using a quantitative approach with purposive sampling, the study examines consumer goods companies on the Indonesia Stock Exchange (IDX) from 2020-2024, with data analyzed via Partial Least Square - Structural Equation Modeling (PLS-SEM). The results showed that GCG has a positive and significant effect on Firm Value and Profitability. In contrast, CSR did not show a significant effect on either. The main finding of this study is that profitability, as measured by Return on Equity (ROE), was proven to significantly mediate the relationship between GCG and Firm Value partially. This indicates that effective GCG mechanisms increase firm value largely through improving financial performance first, which is a positive signal for investors. However, profitability was unable to mediate the relationship between CSR and Firm Value. These findings confirm that, in the context of the Indonesian consumer goods market during the study period, good governance practices were a more fundamental driver of value than social responsibility disclosure. This research contributes to the literatur by confirming the mediating role of profitability in the post-pandemic Indonesian consumer market.